IMPACT OF KNOWLEDGE MANAGEMENT IN DEVELOPING ORGANIZATIONAL COMMITMENT WITHIN JORDANIAN LIBRARIES: MEDIATING INFLUENCE OF IT - Dr. Mohammad Ahmad Niqresh, Dr. Khaldun Al - DWEIRI (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Current study aimed at examining the mediating role of IT infrastructure between KM and the development of organizational commitment within Jordanian libraries. Researchers adopted quantitative approach through depending on a questionnaire as a tool. The questionnaire was distributed in (88) individuals within (10) governmental universities in Jordan. Results of study indicated an influence of KM on OC among sample of study that is attributed to IT infrastructure. Among sub-variables; it appeared that KM practices scored a mean of (3.94) was the most influential on OC compared to KM enablers which scored a mean of (3.92) of influence on IT infrastructure. Study also revealed that IT infrastructure within the library mediates the relationship between KM and OC through easing and paving the way for employees to gain all the knowledge they need and utilize all tools that are able to ease their work and help them perform better. Study recommended working to provide employees with various courses and workshops related to knowledge management concepts and provide clear strategies that support and stimulate the adoption of the concept of knowledge management.